Report of the 38th general assembly - ASEAN Inter-parliamentary organization - Asean Inter- parliamentary assembly, Hội đồng liên nghị viện ASEAN (ASEAN Inter - Parliamentary Assembly (AIPA), 2017)
Hội nghị lần thứ 38 của Tổ chức liên nghị viện ASEAN được tổ chức tại Manila, Philippines từ ngày 14-20 tháng 9 năm 2017.